Measuring Poverty in Forced Displacement Contexts - Utz Pape; Paolo Verme (Global Labor Organization (GLO), 2023)
Poverty measurement among forcibly displaced populations, including refugees and internally displaced persons, has been, for long, neglected by the economics profession and by poverty specialists working across the social sciences. This has changed since the beginning of the Syrian conflict in 2011 and the peak of the European migration crisis in 2015. This paper reviews the evolution, current status, and future prospects of the poverty measurement literature on forcibly displaced populations; discusses the main data and measurement challenges associated with this type of population; illustrates selected empirical findings that have emerged from the recent literature; and provides an overview of the substantial effort that humanitarian and development organizations are currently undertaking to close this historical gap in poverty measurement.
Keywords: I30; I32; 330; poverty; refugees; IDPs